Methodological Investigations in Agent-Based Modelling: With Applications for the Social Sciences - Silverman, Eric (Springer Nature, 2018)
Agent-Based Modelling; ABM; Artificial Intelligence; AI; Computational social science; Social simulation; Population sciences